Geopolitics of the European Rule of Law – Lessons from Ukraine and the Western Balkans - Elise Bernard (Intereconomics, 2022)
Several opportunities arise for rule of law promoters: to reclaim the security discourse; to explain EU enlargement through the commitment to the rule of law; and consequently, to develop a strategy to influence opponents of enlargement.
Keywords: M48; 330